Inventarisasi Tumbuhan Famili Malvaceae di Desa Tabing Rimbah Kecamatan Mandastana Kabupaten Barito Kuala - Muhammad Iqbal Trinajah; Muhammad Zaini; M. Arsyad (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Floristic inventory is a fundamental step in biodiversity conservation, especially for ecologically and economically valuable families such as Malvaceae. This study aims to document the species richness of Malvaceae in the wetland ecosystem of Tabing Rimbah Village, Barito Kuala Regency. The research method used was an exploratory survey in swamp, forest, and residential habitat types. Sampling was conducted purposively on every individual encountered. Species identification was performed morphologically by matching key characters to standard taxonomic literature such as Flora of China and PROSEA, and cross-validation using the iNaturalist digital platform. The inventory results identified 10 species in 7 genera with varying habitus of herbs, shrubs, and trees. Melochia corchorifolia and Hibiscus tiliaceus were recorded as dominant species widespread along swamp and river banks, indicating strong ecological adaptation to water level fluctuations. These findings provide the first baseline data for the Malvaceae family at the site, confirming its scientific value as documentation of floristic diversity essential for conservation strategies and sustainable management at the local level.